Engineering a bifunctional copper site in the cupredoxin fold by loop-directed mutagenesis. Issue 32 (19th July 2018) - Espinoza-Cara, Andrés; Zitare, Ulises; Alvarez-Paggi, Damián; Klinke, Sebastián; Otero, Lisandro H.; Murgida, Daniel H.; Vila, Alejandro J.
Abstract : Loop directed mutagenesis leads to a cupredoxin withthe strongest copper–thiolate bond known to date, high reduction potential and imidazole binding properties. Abstract : Copper sites in proteins are designed to perform either electron transfer or redox catalysis. Type 1 and CuA sites are electron transfer hubs bound to a rigid protein fold that prevents binding of exogenous ligands and side reactions. Here we report the engineering of two Type 1 sites by loop-directed mutagenesis within a CuA scaffold with unique electronic structures and functional features. A copper–thioether axial bond shorter than the copper–thiolate bond is responsible for the electronic structure features, in contrast to all other natural or chimeric sites where the copper thiolate bond is short. These sites display highly unusual features, such as: (1) a high reduction potential despite a strong interaction with the axial ligand, which we attribute to changes in the hydrogen bond network and (2) the ability to bind exogenous ligands such as imidazole and azide. This strategy widens the possibility of using natural protein scaffolds with functional features not present in nature.